Measuring the Effectiveness of Promotion Strategies in Enhancing the Distinctiveness of Mamasa Cultural Tourism: Optimization of E-WOM and Digital Media - Dian Rahmayanti Rivai; Irawati Irawati; Futri Ayu Wulandari; Nur Ariyandani; Rahmat Ghazali (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to evaluate the effectiveness of digital promotion strategies in enhancing the cultural distinctiveness of Mamasa as a tourism destination. It specifically examines the role of digital media and electronic word-of-mouth (EWOM) in shaping tourists’ perceptions of cultural uniqueness. Using a qualitative approach with transcendental phenomenology, data were obtained through in depth interviews, digital ethnography, and documentation involving local tourism officials, destination managers, and tourists. Thematic analysis using NVivo 14 was applied within the EPIC (Empathy, Persuasion, Impact, Communication) framework. The results revealed six dominant themes: emotionally resonant local content enhances empathy; persuasive storytelling strengthens engagement; authentic digital narratives influence visitation intention; limited interactivity reduces communication effectiveness; strong perception of cultural distinctiveness heightens interest; and E-WOM amplifies credibility and promotional reach. The study concludes that effective cultural tourism promotion requires authentic, emotionally engaging, and participatory digital strategies supported by active two way communication. Strengthening collaboration between local governments, tourism managers, and communities is essential to optimize the strategic potential of digital media and E-WOM in reinforcing Mamasa’s cultural identity and tourism appeal.